How should libraries respond to new forms of publication? Some reflections on the expectations of users and providers and what could be realized at the present state of technical development - Schmiede, Rudi; Stoll, Julia; Sonkajärvi, Hanna; Körnig, Stephan (2003)
Abstract: "The paper focuses on the possibilities and problems created for the humanities by the usage of Digital Libraries. The exchange of information, forms of discussion and the process of publication in the scientific communities have changed over the recent years. On the other hand the user group of digital libraries is heterogeneous and difficult to define. We discuss the organization structure and the working process of two communities, which have quickly adapted their communication process to the use of web-technologies: the Open Source community and the scientific research community. We have to distinguish the communication technique, the applications of the World Wide Web (WWW), including search engines, and the barely started developments to realize new Web Services for DL-oriented applications, to support the library services and finally to obtain a new concept, which we call long-term access to digital structured resources by contract. A DL user views a Web Service as a 'black